Misconduct and disciplinary action: proportionality of punishment with reference to industrial court awards - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2016)
In determining the appropriate punishment for the alleged misconduct, the company is entitled to consider the aggravating circumstances that count against the employee, such as the seriousness of the offense, his position in the company, to what degree did any element of trust exist in this employment relationship. The extenuating circumstances such as self-defense, provocation, coercion, lack of intent and necessity, among others things is also considered. Further, the mitigating circumstances in favour of the employee that should be considered include the employee’s length of service, his position in the company, his previous work and disciplinary record, does he show any remorse and if so to what degree, is he prepared to make restitution if this is possible, did he readily plead guilty and confess, among other things.1 Only after careful consideration of the above circumstances would the inquiry panel arrive at a suitable and fair sanction. The company must act reasonably in deciding whether the misconduct warrant dismiss. When a dismissal claim under s 20 of the Industrial Relations Act 1967 (IRA) is referred to the Industrial Court, the court will have to determine, inter alia, whether the dismissal was with just cause or excuse and whether the preferred sanction was proportionate to the gravity of the wrong committed. The principle of proportionality demands that the alleged misconduct of the claimant and the punishment meted out on him must be proportional to his culpability in doing what he did. In other words, there must be proportionality between the severity of the misconduct and discipline or dismissal imposed on the claimant.2 In light of the above, this article discusses the principle of proportionality of punishment in dismissal cases with reference to the awards of the Industrial Court.